Microarray Transcription Profiling of a Shewanella oneidensis etrA Mutant - Beliaev, Alex S. (American Society for Microbiology, 2002)
DNA microarrays were used to examine the effect of an insertional mutation in the Shewanella oneidensis etrA (electron transport regulator) locus on gene expression under anaerobic conditions. The mRNA levels of 69 genes with documented functions in energy and carbon metabolism, regulation, transport, and other cellular processes displayed significant alterations in transcript abundance in an etrA-mutant genetic background. This is the first microarray study indicating a possible involvement of EtrA in the regulation of gene expression in S. oneidensis MR-1.